NECESSITY OF VIRTUAL MODES FOR LEARNING ENGLISH LANGUAGE IS INEVITABLE IN THE MODERNIZED SOCIETY. (International Journal of Food and Nutritional Sciences, 2022)
The landscape for language learning has changed significantly after the invention of digital devices. It is a significant transformation happened in the field of language learning centers. Technology made easy access to everything through online modes. Virtual learning environments, leveraging tools like video conferencing, learning management systems (LMS), and immersive technologies such as virtual reality (VR), have become pivotal in teaching English as a second language since (ESL).